PENINGKATAN KUALITAS HIDUP MASYARAKAT DENGAN PENINGKATAN KESADARAN AKAN PENTINGNYA KESEHATAN DI KELURAHAN BENDUL MERISI - Aris, Bernardus; Priskila, Onny; Indrawati, Lilik; Mufida Sari, Laili (Jurnal Abdimas Musi Charitas, 2023)
The background of the community service program is to increase awareness of the community, especially the elderly, of the importance of health. Health is important, especially for the elderly who have experienced a decrease in the strength of organ function. Therefore, self-awareness is the key to improving the quality of personal health. Self is basically an individual who is responsible for their own health. Increased awareness is expected to help the community (elderly) to be more sensitive to their own health, and try to anticipate or overcome diseases, such as hypertension, uric acid, cholesterol, and diabetes. The method used in this community service is health counseling with health checks and counseling based on the results of health checks. The results of this community service program, namely the participants (elderly) know the current health condition, and can anticipate the worsening of the disease suffered.